Do birds of a feather always flock together? A multidimensional examination of homophily in crowdfunding - Markus Klepsch (Junior Management Science (JUMS), 2023)
Homophily—the tendency of individuals to associate with similar others—is one of the most persistent findings in research on interpersonal interaction. Literature has recently also studied the impact of homophily in crowdfunding markets (Greenberg & Mollick, 2017). While these results offer valuable insights into the dimension sex, homophily is a multidimensional con-struct in theory (McPherson, Smith-Lovin, & Cook, 2001). Therefore, I employ homophily theorizing by analyzing to what extent homophily influences backers' choices in crowdfunding regarding five different sociodemographic dimensions. To test my hypotheses, I drew upon a unique dataset of roughly 3.5 million backings made on the crowdfunding platform Indie-gogo. My results suggest that individuals make homophilic choices with respect to age, sex, occupation, and location. While my findings thus confirm that, in large, homophily plays an essential role in individual choices, I extend the literature by showing that it is not always as clear-cut. The more complex the dimension, the more difficult it is to judge. Specifically, I show that in the dimension race, where a plethora of possible combinations leads to a certain degree of complexity, there is no simple 'yes' or 'no' answer to whether homophily influences the decision. Instead, significant differences can be observed depending on the specific race under consideration.
Keywords: 650; Crowdfunding; Indiegogo; Homophily